KEBIJAKSANAAN KEPENDUDUKAN: TEORI, KONSEP, DAN PENERAPANNYA DI INDONESIA - Tadjuddin Noer Effendi (Populasi, 1991)
This paper discusses the theoritical, conceptual background of population policy in Indonesia. In particular, it discusses the theory that related to the population control especially the fertility and mortality. It also suggests that fertility can be reduced by implementing family planningprogram and to reduce infant mortality. The populationproblems notonly government care,but also public responsibility in order to save the environment for the next generation.